2005
DOI: 10.1071/fp05047
|View full text |Cite
|
Sign up to set email alerts
|

Potential yield and water-use efficiency benefits in sorghum from limited maximum transpiration rate

Abstract: Limitations on maximum transpiration rates, which are commonly observed as midday stomatal closure, have been observed even under well-watered conditions. Such limitations may be caused by restricted hydraulic conductance in the plant or by limited supply of water to the plant from uptake by the roots. This behaviour would have the consequences of limiting photosynthetic rate, increasing transpiration efficiency, and conserving soil water. A key question is whether the conservation of water will be rewarded by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
187
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(201 citation statements)
references
References 35 publications
11
187
3
Order By: Relevance
“…Reduced transpiration by stomata closing, in plants under severe soil moisture stress, may be a desirable characteristic in soybean plants cultivated without irrigation, especially in arid regions, in order to save water in the initial stages of the crop, which enables a water supply to be available for later stages when water is most needed (Sinclair et al, 2005). Therefore, since the cultivars of indeterminate habit showed greater values of stomata conductance and CO 2 assimilation, under severe drought treatment, they could also reach the wilting point more quickly.…”
Section: Resultsmentioning
confidence: 99%
“…Reduced transpiration by stomata closing, in plants under severe soil moisture stress, may be a desirable characteristic in soybean plants cultivated without irrigation, especially in arid regions, in order to save water in the initial stages of the crop, which enables a water supply to be available for later stages when water is most needed (Sinclair et al, 2005). Therefore, since the cultivars of indeterminate habit showed greater values of stomata conductance and CO 2 assimilation, under severe drought treatment, they could also reach the wilting point more quickly.…”
Section: Resultsmentioning
confidence: 99%
“…It was then argued that a lower canopy conductance would lead to higher transpiration efficiency (Sinclair et al 2005). There was indeed a close relationship between a lower TR and a higher TE under high VPD conditions and both water treatments (R 2 = 0.40 and 0.76 under WW and WS respectively; Fig.…”
Section: Genotypic Differences In the Transpiration Rate Response To mentioning
confidence: 97%
“…Therefore, in genotypes that would restrict TR, especially at high VPD, there is a scope for water saving which would then be available and essential for grain filling late in the season (Sinclair et al 2005;Ghoolipoor et al 2010;Kholova et al 2010a, b;Zaman-Allah et al 2011a, b). It was then argued that a lower canopy conductance would lead to higher transpiration efficiency (Sinclair et al 2005).…”
Section: Genotypic Differences In the Transpiration Rate Response To mentioning
confidence: 99%
“…However, genotypic variation has only recently been revealed in different species such as soybean (Fletcher et al 2007;Sadok and Sinclair 2009), chickpea (Zaman-Allah et al 2011b), cowpea (Belko et al 2012), peanut (Devi et al 2010) and cereals such as sorghum (Gholipoor et al 2010) and pearl millet (Kholová et al 2010b). Crop simulation analysis has shown that this maximum rate of transpiration would have a beneficial effect on yield and also that it would lead to water saving and a higher TE (Sinclair et al 2005). In the case of cowpea, this trait was used to discriminate terminal water stress-tolerant from sensitive entries (Belko et al 2012).…”
Section: Leaf Canopy Conductancementioning
confidence: 99%